The Village Secretary's Strategy for Coordinating Village Officials in Conducting Village Deliberations - Mohamad Yusup; Nazmudin Nazmudin; Ujang Saepudin (ijd-demos, 2024)
Abstract The core issue of this study concerns the role of the Village Secretary—a village official whose duties include coordinating all village officials during the village deliberation process. The research question addresses the strategies employed by the Village Secretary to coordinate village officials in organizing village deliberations in Umbulan Village, Cikeusik District, Pandeglang Regency, while also examining the influencing factors. To address this research question, a qualitative research method with a descriptive approach was selected. Data collection involved structured interviews and participatory observation to obtain primary data, alongside documentation techniques for secondary data. Informants were selected using purposive sampling, specifically the "key person" technique. The study concludes that the factors influencing coordination among village officials during village deliberations are: (a) the superior's leadership style, (b) personal relationships among officials, (c) a sense of togetherness among officials, (d) the officials' understanding of their duties, (e) the theme, agenda, or issues being discussed, and (f) the accumulation of work tasks. Meanwhile, the strategies implemented include: (a) enhancing effective communication with subordinates and colleagues, (b) providing rewards to subordinates, (c) discussing work matters democratically, and (d) fostering a sense of kinship and togetherness among the village officials. Keywords: Village Secretary, Village Officials, Coordination, Village Deliberation